Contemporary Drug–Drug Interactions in HIV Treatment. Issue 6 (25th March 2019) - Devanathan, Aaron S.; Anderson, Daijha J.C.; Cottrell, Mackenzie L.; Burgunder, Erin M.; Saunders, Ashley C.; Kashuba, Angela D.M.
Abstract : Despite development of modern antiretrovirals with lower drug interaction potential than their predecessors, drug interaction challenges remain. Standard treatment regimens still require multiple antiretrovirals that may cause, or may be the target of, drug interactions. Additionally, people living with HIV are living longer and often present with comorbid conditions that require concomitant long‐term drug therapy. Also, treatment of infectious diseases in resource‐limited settings can result in significant interactions. In this review, we describe absorption, distribution, metabolism, and excretion pathways as they relate to relevant drug interactions with antiretrovirals along with the potential clinical consequences of these interactions. We highlight clinical data that illustrate pertinent interactions and provide tools to assist in predicting drug interactions in the absence of clinical data. Given these tools and thoughtful consideration of drug combinations, drug therapy in people living with HIV can be safely and effectively managed throughout their lifetime.